PECULIARITIES OF INDIVIDUAL MOBILE ACTIVITY OF STUDENTS OF PEDAGOGICAL SPECIALTIES - Redkina, Mariia (Mountain School of Ukrainian Carpaty, 2019)
Due to the constant scientific and technical development of society, there is a lack of motor activity in students of institutions of higher education, which in most cases is the cause of various diseases. The article analyzes the problem of organizing motor activity of students of pedagogical specialties. It is emphasized that motor activity of student youth is considered as an integral part of life activity. It is stated that the structure of motor activity is multifaceted and individualized for each individual. It describes how students organize their leisure activities in terms of mental employment. The main reasons that contribute to the development of hypodynamia among student youth have been identified. The level of motor activity of students of pedagogical specialties is investigated. Practical experience shows that students of pedagogical specialties are not able to fully organize their motor activity. The question of optimal motor regimes, their volumes and intensity has been well studied in relation to the method of training athletes. A special role in this problem is played by the organization of the motor mode of students of pedagogical specialties, the training of which is connected with the low motor activity. Chronic impaired motor activity in the mode of student youth becomes a real threat to her health and normal physical performance. It is emphasized that the options for solving this problem are possible due to the intensive use of all means of physical culture. It is summarized that the majority of students of pedagogical specialties lead a sedentary lifestyle that affects the psychoemotional and somatic state of students as a result of low or moderate physical fitness. Implementation of programs of physical and health classes, which are based on stimulation of motivation to systematic physical exercises, will help to attract students to physical activity.